First report of the Anti-Inflation Task Force : October 1975 - Federal Ministry of Information, Nigeria; Federal Ministry of Information, Nigeria (Lagos : Federal Ministry of Information, Printing Division, 1975)
This volume consist of the report of the Anti-inflation Task Force appointed by the Federal Military Government on the 15th of August, 1975.
Cover title.
At head of title: Federal Republic of Nigeria.
Includes bibliographical references.
lje 7/3/19
Arch
Keywords: Inflation (Finance); Wage-price policy; Nigeria